The Contribution of Teachers’Motivation and Characteristics on the Teachers’ Performance in Junior High School of Maarif Metro Lampung - Mashari, Ali; Umami, Ida (International Journal for Educational and Vocational Studies, 2019)
The success of the teacher in the teaching and learning process is determined by the teacher's performance as an educator. This performance plays an important role in achieving optimal teaching goals. However, in the reality of the teacher's performance shows less encouraging symptoms that many teaching teachers seem to have the lack mastery in teaching materials, media and methods used in the teaching and learning process. They have a tendency to teach the same materials in the following year while some of teachers arestill not being placed in accordance with their educational background. There is also the lack of encouragement from teachers to excel and compete among others. This research is conducted to reveal the contribution of teachers’ motivation and characteristic toward their performance in SMP Ma’arif Metro. The research method used in this research is the quantitative method using Ex Post Facto. The population of this study was all of teacheras many as 38 people and the sampling technique was done by total sampling. The result of the research shows that the teachers’ Motivation is 79.4 % of the ideal maximum score and can be categorized as medium category.Teachers’ motivation contributes significantly towardTeacher’s performance by 41.2 %. While the Teachers’ Characteristics score is 85.30 % of the ideal maximum score and can be categorized as good category.Teachers’ Characteristics contribute significantly towardthe Teachers’ Performance by 28.1 %, while Teachers’ Motivation and Characteristics together contribute significantly toward Teachers’ Performance by 32.7 %. This study found out that the two predictor variables which are the Motivation and Characteristics of Teachers both individually and jointly made a meaningful contribution toward the Teachers’ Performance.